In vivo study of human Plasmodium knowlesi inMacaca fascicularis - Anderios, Fread; NoorRain, Abdullah; Vythilingam, Indra (Elsevier, 2010)
Plasmodium knowlesi is a malaria parasite of Old World monkeys and is infectious to humans. In this study Macaca fascicularis was used as a model to understand the host response to P. knowlesi using parasitological and haematological parameters. Three M. fascicularis of either sex were experimentally infected with P. knowlesi erythrocytic parasites from humans. The pre-patent period for P. knowlesi infection in M. fascicularis ranged from seven to 14 days. The parasitemia observed was 13,686–24,202 parasites per μL of blood for asexual stage and 88–264 parasites per μL of blood for sexual stage. Periodicity analysis adopted from microfilaria periodicity technique of asexual stage showed that the parasitemia peak at 17:39 h while the sexual stage peaked at 02:36 h. Mathematical analysis of the data indicates that P. knowlesi gametocytes tend to display periodicity with a peak (24:00–06:00) that coincides with the peak biting activity (19:00–06:00) of the local vector, Anopheles latens. The morphology of P. knowlesi resembled P. falciparum in early trophozoite and P. malariae in late trophozoite. However, it may be distinguishable by observing the appliqué appearance of the cytoplasm and the chromatin lying inside the ring. Haematological analysis on macaques with knowlesi malaria showed clinical manifestations of hypoglycaemia, anaemia and hyperbilirubinemia. Gross examination of spleen and liver showed malaria pigments deposition in both organs.